Improvement of Nonlinear Optical Properties for Mixture Laser Dyes Doped PMMA - Mahdi, Zainab F. (Iraqi Journal of Laser, 2010)
The spectral characteristics and the nonlinear optical properties of the mixed donor (C-480) acceptor (Rh-6G) have been determined. The spectral characteristics are studied by recording their absorption and fluorescence spectra. The nonlinear optical properties were measured by z-scan technique, using Q-switched Nd: YAG laser with 1064 nm wavelength. The results showed that the optimum concentration of acceptor is responsible for increasing the absorption and the emission bandwidth of donor to full range and to 242 nm respectively by the energy transfer process, also the efficiency of the process was increased by increasing the donor and acceptor concentration. The obtained nonlinear properties results of the mixture C-480/ Rh-6G showed a negative nonlinear refractive index and reverse saturation absorption. All the nonlinear optical parameters are linearly dependent with concentration. The origin of optical nonlinearity in the dye may be attributed to laser-heating induced nonlinear effect. Results show that mixture of laser dyes are effective nonlinear optical materials as compared to individual laser dyes.